The influence of brand image price and location on product purchase decision on JCo donuts products - Yolanda Yadita Mahmud; Primaraga Sumantri Indra Wicaksana (Enrichment : Journal of Management, 2023)
This study aims to examine Brand Image on purchasing decisions, price on purchasing decisions, and location on purchasing decisions on J.Co Donuts products. Product purchasing decisions are directly influenced by the company's brand image, consumers decide to buy a product based on the price and location of a brand or product. This research uses quantitative methods. Data collection in this study uses questionnaire data and literature studies with a population of customers who have purchased J.Co Donuts. Sampling using nonprobability sampling method with accidental sampling technique with a sample size of 100 respondents who are consumers who have purchased J.Co Donuts products. This research uses SPSS software version 22. To collect data, including observation of the distribution of questionnaires and literature studies. The analysis methods used are validity test, reliability test, classical assumption test, multiple linear analysis and hypothesis testing. The findings of the research prove that the brand image variable does not have a significant influence between brand image on purchasing decisions. The price variable has a significant effect on purchasing decisions. The location variable has no significant effect on purchasing decisions.